(untitled) (The Journal of Psychology and Sociology, 2014)
The article presents techniques of NLP consulting based on the Model strategies of NLP. The model strategies of NLP describes strategies that cause disorders and pathological conditions in people’s lives, but also suggests ways of overcoming them and the necessary skills. Red thread on article is the idea that in NLP the process of helping people to change their personality disorders is the process of changing their life strategies. Details such techniques as «Embedding new strategy», «Changing sub modalities, «Change the physiological context» and « «Using tasks». The authors show that the purpose of NLP techniques in working with personality disorders is to reduce the level of anxiety, depression, paranoia, aggression, to overcome deep personal problems caused post-traumatic stress disorder. And this in turn should contribute to the removal of suicidal aspect of the structure of personality advise. The analysis of researches of foreign scientists and acquaintance with excerpts from their works allowed the authors to come to the belief that customers experienced the effect of NLP, more responsible attitude to their lives and have more effective life skills. The article will be interesting for specialists in NLP and psychotherapy, school psychologists, and anyone interested in modern methods of changing behavior, development and harmonization of personality.